TGT damages its substrate tRNAs by the formation of abasic sites in the anticodon loop - Kopietz, Kevin; Raorane, Kasturi; Guo, Wei; Flegler, Florian; Bourguignon, Valérie; Thuillier, Quentin; Kilz, Lea-Marie; Weber, Marlies; Marchand, Virginie; Reuter, Klaus; Tuorto, Francesca; Helm, Mark; et al. (Journal of molecular biology, 2025)
RNA modification is a well-recognized way for gene expression regulation in a living cell. Natural enzymatic RNA modifications have been characterized for decades. Recently, additional mechanisms, more related to RNA damage, have emerged, which do not involve targeted enzymatic activity but nonetheless alter the chemical structure of nucleosides. Aberrantly modified RNA may also appear due to incomplete or erroneous enzymatic reactions. We demonstrate that tRNA-guanine transglycosylase (TGT) in bacteria and eukaryotes accidentally leaves RNA abasic sites (rAP) in the anticodon loop of substrate tRNAs. The formation of an rAP site is a part of the TGT catalytic mechanism, involving the cleavage of the N-glycosidic bond, and the formation of a covalent enzyme-tRNA adduct. The phenomenon of rAP site formation is readily detectable for tRNATyr(GUA) in bacteria and tRNAAsp(GUC) in eukaryotes and is amplified when the supply for preQ1 in bacteria is compromised. The TGT-mediated accumulation of rAP sites in tRNAs is strongly induced upon stress, and most prominent upon oxidative stress in bacteria. Polysome profiling in bacteria points out the partial exclusion of rAP-containing tRNAs from the translating ribosome fraction, prompting a consideration of these tRNA species as “damaged” and most likely non-functional. The exploratory analysis of rAP tRNA(GUN) sites in mice demonstrates a substantial variability among different tissues, with the highest accumulation of damaged tRNA observed in the brain, the lung and the spleen. Altogether, these results uncover a unique molecular mechanism of RNA modification that, via a presumably erroneous reaction, diminishes RNA function rather than enhancing it.
Online verfügbar: 26. Februar 2025, Artikelversion: 10. Juni 2025
Gesehen am 19.08.2025